Desenvolvimento de técnicas de análise plástica e de otimização de peso de estruturas via programação linear - Paulo Eustaquio Raso (1991)
The aim of the present work is to present a novel technique for plastic analysis (limit anlysis) of framed structures, based on a kinematic principles (Upper Bound Theorem). The technique consits of transforming the structural problem into an optimization problem, which is solved by Linear Programming. The solution of the problem is obtained by optimizing the load function applied to the structure which is subjected to a set of restrictions such like the equations of equilibrium and the inequalities. The solution of the problem is presented as collapse load factor, and the corresponding mechanism of collapse. This work also encompass the automatic definiton of the equations of equilibrium for modular retangular framed structures and a similiar technique developed for minimum weight design. The minimum weight design technique was formulated based on the weight compatibility mechanism and the Foulkes Theorem. The problem is solved in a similar form to the previous one. The automatic calculations are obtained through a computational program developed in FORTRAN for this purpose.